2019
DOI: 10.1016/j.geomorph.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Downstream fining in a megaclast-dominated fluvial system: The Sabeto River of western Viti Levu, Fiji

Abstract: Megaclast-dominated fluvial systems have been largely ignored by researchers. Yet megaclasts exert an important control on channel geomorphology, flow behaviour and sediment transport, and such systems are probably far more common than this neglect would suggest. Despite the explicit identification of megaclasts as the products of cataclysmic flow, observation of modern fluvial systems confirms that megaclasts can be entrained by flows that lie within the normal flow regime. The pattern of fining along the meg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…1 ). The Sabeto River is an active, bedload transporting, gravel-bed system [3] . The lithology of the river gravels reflects the make-up of the rocks exposed in the catchment.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). The Sabeto River is an active, bedload transporting, gravel-bed system [3] . The lithology of the river gravels reflects the make-up of the rocks exposed in the catchment.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…1 The geology of the catchment of the Sabeto River of western Viti Levu, Fiji, showing the location of the sampling stations. Modified from Gale et al [3] .
Fig.
…”
Section: Data Descriptionmentioning
confidence: 99%
“…Particularly, geomorphologists deal with modern sediments and depositional environments, and huge detrital rock particles often constitute either small-scale landforms or elements of bigger landforms. Surprisingly, the term "megaclast" and the other relevant terms (e.g., the term "block") are not used in the high-class geomorphological studies as frequently, as one would expect (e.g., [54]). Many influential articles mention boulders, although their figures illustrate true megaclasts.…”
Section: Putting Into the Broader Contextmentioning
confidence: 99%
“…River sediment grain size is one of the characterizing indicators of river hydrodynamic conditions and transport environment (Knighton, 1999), and its size and distribution characteristics are related to many factors such as regional geology, geomorphology, climate and hydrology (Allen, 2008;Duller et al, 2010;Blom et al, 2017). Fluvial abrasion and sorting of the reconstituted population, in the absence of further inputs, often produces relatively systematic downstream fining trends (Sternberg, 1875;Yatsu, 1955;Gale et al, 2019;Ivan and Tomáš, 2021a). Sternberg (1875) suggested that abrasion is the main cause of sediment decomposition and grain size refinement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, affected by the characteristics of the tributary sediments, the inflow of the tributary can cause the coarsening or refinement of the main stream channel sediment (Blom et al, 2017;Ivan and Tomáš, 2021b). Abrasion and sorting also have different effects on the refinement of river sediments in different river sections (Gale et al, 2019). The Shiyang River Basin (SYRB), which is an inland river system in Northwestern China, provides a good case for comprehensive comparative analysis of the impact of the above factors on the channel sediments.…”
Section: Introductionmentioning
confidence: 99%